The relationship between good governance and administrative corruption - منهل إلهام عبدال; رمضان أحمد رشيد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This study has dealt with the relationship between the “Good Governance” and “Administrative Corruption”. In order to detect and highlights this relation, the study has been divided into four majors sections: Section one dealt with the methodological framework of the research, section two focused on “good governance” subject, while section three was devoted to “administrative corruption”, section four shed lights on the relationship between the good governance and administrative corruption. Moreover, the introduction, the conclusion, documentation, and references have been tackled with. The focal point problem of the research emerged by asking the question: what kind of relationship is there between good governance and administrative corruption? To solve and find an answer to this question, the researcher has reconstructed and broken down the main question into divided small queries such as: what is meant by a good governance? What are its main requirements and criteria? What is meant by the notion of administrative corruption? What are the reasons and motives behind this notion? And finally, how will good governance deal with administrative corruption? This study has tried to achieve a number of aims through showing the notion of good governance and its basic principles by identifying both type and nature of the relationship between good governance and administrative corruption and also by getting acquaintance with the role and the type of governance specifically good governance which activates the developmental and economic performance for the country. Furthermore, by giving recommendations which aid and help to simplify the application of principles of good governance. Besides, presenting suggestions which delimit the dominance of administrative corruption. To sum up, the study has reached the following conclusions: the wise and good governance that is based on a dialogue between the rulers and people as well as by expanding the potentials and capabilities of citizens to freely select and participate in effective techniques for accountability and oversight in accordance with provisions of the law, plays an essential role in enabling legal environment to establish a democratic system of the government to achieve administrative advice to eliminate all forms of administrative corruptions through a number of techniques such as popular and wide spread participation in the governance through institutional representative legitimacy and activating the role of civil organizations in making decisions or real participation for getting information. International institutions pay attention to the relationship between good governance and administrative corruption. They adopt and rely on the wise governance as active syllabus to eliminate the administrative corruption. Since administrative corruption is regarded as a major hindrance which stands against the development process, and also the greater the corruption is, the greater backwardness of countries will be. Hence these push the researchers, institutions and countries to look for active techniques to eliminate it. Due to this, it is commonly agreed on establishing the dominance and combat of good governance upon the administrative corruption as this type of governance, i.e.,( good) adopted active mechanisms and procedures to eliminate the corruption. There is a mutual conflict between the good governance and administrative corruption. Whenever the conditions and requirements of the wise governance are met, there will be effective ways to fight corruption, and when the requirements of good governance are absent, administration corruption will be spread and expanded eventually become unavoidable. Therefore, the major hypotheses of the research have been validated under the heading: “there is an adverse relationship between good governance and administrative corruption”.